Rancang Bangun Media Pembelajaran Interaktif Pengenalan Obat Antibiotik Berbasis Android - Fatimah, Dini Destiani Siti; Satria, Eri; Aulia, Wafa Ghaida (Jurnal Algoritma, 2025)
Learning antibiotic drugs at the Pharmacy Vocational School is relatively difficult because these drugs have many classes and the use of scientific terms. To overcome this, interactive learning media involving images, animations, text, and sound is needed so that the material can be learned more easily. Therefore, the Android-based antibiotic drug introduction learning media application was created to help vocational school students majoring in pharmacy in learning antibiotic materials that can be used anywhere and anytime. The methodology used in the creation of this application is the MDLC (Multimedia Development Life Cycle) methodology, while the evaluation of the application is carried out using the EUCS (End User Computing Satisfaction) method. The antibiotic introduction learning media application has material features, quizzes, instructions, about and audio pronunciation of scientific terms so that users can understand the pronunciation well. The results of the evaluation of the application obtained a user satisfaction level with an average of 98% which is included in the very satisfied category.